Evidence of human exposure and associated risk factors to Rift Valley fever in selected districts of Central and Western Zambia - Chilufya C. Kasongamulilo; Michelo Syakalima; Ngondo Saasa; Henson Kainga; Girja S. Pandey; Andrew N. Mukubesa; Innocent Mwape; Masahiro Kajihara; Ayato Takada; Martin Simuunza (PLoS ONE, 2025)
Rift Valley fever (RVF) is an important viral zoonotic disease that not only affects ruminants but causes serious morbidity and mortality in humans. In humans, its symptoms range from mild flu-like signs to a severe form such as retinal damage, meningoencephalitis to haemorrhagic fever. In this study, 202 human serum samples were collected from central and western parts of Zambia and tested for RVF-specific antibodies using a commercially available ELISA kit. A pre-tested semi-structured questionnaire was used to collect data for determining hypothesised risk factors for exposure to RVF. The participants enrolled in this study, were only those who are at high risk of RVF infection and were in close contact with animals and animal products. The study revealed an overall seropositivity of 9.90%, occupationally distributed as 16.67% among slaughter house workers, 14.41% among livestock farmers, and 0% among the others (i.e., students, butchery, and farm workers). The prevalence was highest (19.23%) in Sesheke district found in the western part of Zambia, while Chisamba district in central Zambia had the lowest prevalence (1.41). Movement of animals in search of greener pastures was identified as a risk factor to being RVF-seropositive. This suggests that there was silent circulation of the virus in the interepidemic period in the study areas. Therefore, this study recommends that public education of livestock farmers, public health workers, slaughterhouse workers, communities, livestock and veterinary staff needs to be enhanced to increase awareness and preparedness for RVF outbreak in Zambia.